THE CAUSE OF BIOMASS EXTINCTION AT THE FRASNIAN-FAMENNIAN BOUNDARY, THE KERMAN PROVINCE SOUTHEASTERN, CENTRAL IRAN (Journal of Sciences, Islamic Republic of Iran)
About 35 samples were collected from lower and upper parts of the proposed Frasnianamennian boundary in three sections of Upper Devonian marine sediments of the Kerman province. The biostratigraphical and geochemical studies indicate that about 45% extinction of brachiopods probably caused by the Frasnian-Famennian bioevents, which is slightly higher than thr rate of Devonian-Carboniferous extinction elsewhere. The results of isotopic carbon and oxygen isotope analysis (? 13C%0 VPDB and ? 10O %VPDB) show a sudden decrease at the proposed Frasnian-Famennian extinction boundary which is followed by positive values above this horizon. The negative excursion may indicate a biomass extinction due to either a meteorite impact or decay of organic matter. The isotopic variations are correlated with those of faunal changes and their extinctions in the area.